International Trade, Hedging and the Demand for Forward Contracts - Jens Eisenschmidt; Klaus Wälde (University of Würzburg, Department of Economics, 2006)
One of the main results of the literature on the effects of uncertainty on trade states that uncertainty should not matter in the presence of well developed forward markets. Empirical studies, however, do not support this result. We derive the demand for forward cover in a small open economy with terms of trade uncertainty. Adopting a standard and more realistic decision structure than the one usually used in this literature, we find that risk averse agents will not buy forwards at an unbiased price. Agents treat forward contracts as an asset rather than as an insurance. This is the reason why, when calibrating the model, only 17% of imports are covered by forwards.
Keywords: F30; F00; G10; 330; Termingeschäft; Hedging; Außenwirtschaft; Theorie; Deutschland